Expectations and Attraction Preferences of Gen Z Tourists: A Case Study of Kampoeng Eropa Malino - Nur Hikmah Zainal; Mandasari Mandasari; Riska Amalia Nasfat; Nurul Atirah; Nur Airun Nisa (Public Resource Innovation Management and Excellence, 2026)
This research is motivated by the increasing trend of thematic tourism based on artificial attractions, which has developed alongside Generation Z's preference for tourism experiences that are aesthetic, fast, and easily shared through digital media. Kampoeng Eropa Malino was chosen as the study object due to its popularity among young tourists, yet it has never been academically studied regarding how Gen Z forms expectations and preferences towards the attractions offered. This study aims to analyze Gen Z's expectations and preferences regarding visual, thematic, and facility attractions, as well as spatial experiences at the destination. Using a descriptive qualitative method, data were collected through the experience stories of three Gen Z informants who had visited more than twice and the researcher's direct observations at the location. The analysis was carried out by categorizing the informants' experiences, comparing them with field conditions, and interpreting them through a framework of push and pull motivations in tourist behavior. The results of the study indicate a gap between Gen Z's visual expectations shaped by digital media and the actual experiences at the location. The Europe theme was considered not immersive, the variety of photo spots was limited, and facilities, including culinary options and accessibility, were deemed insufficient to meet the needs of young tourists. These findings suggest that Gen Z's internal motivations do not result in satisfaction when external attractions do not meet their aesthetic and comfort standards. The novelty of this research lies in its focus on medium-scale artificial thematic destinations and how Gen Z interprets visually and thematically based tourism experiences.